Rationale, design and baseline characteristics of participants in the OCEANIC-STROKE trial of FXIa inhibition for secondary stroke prevention - Sharma, Mukul; Dong, Qiang; Hirano, Teruyuki; Kasner, Scott E.; Saver, Jeffrey; Masjuan, Jaime; Demchuk, Andrew M.; Cordonnier, Charlotte; Bereczki, Daniel; Tsivgoulis, Georgios; Veltkamp, Roland; Staikov, Ivan; et al. (Oxford University Press, 2026)
INTRODUCTION: Genetic deficiency of factor XI is associated with a reduced risk of ischemic stroke. Asundexian is a direct inhibitor of activated factor XIa (FXIa) with a low risk of bleeding in early trials. We seek to determine its efficacy and safety combined with antiplatelet therapy for prevention of ischemic stroke. PATIENTS AND METHODS: Oral faCtor Eleven A iNhibitor asundexian as novel antithrombotiC (OCEANIC-STROKE) is a placebo-controlled, double-blind, event-driven randomised trial including participants with stroke (NIHSS ≤ 15) or high-risk TIA (ABCD2 6 or 7) within 72 h of onset. Participants had at least one of the following: atherosclerosis of extra- or intracranial vessels, a medical history of atherosclerosis or an imaged acute non-lacunar infarct. We excluded sources of stroke requiring anticoagulation and active non-trivial bleeding other than hemorrhagic infarction (HI 1 or 2). Participants received asundexian 50 mg daily or placebo stratified by planned concurrent antiplatelet therapy (single vs dual). The primary endpoint is time to ischemic stroke. We present baseline characteristics as of 5 June 2025. RESULTS: Between January 2023 and February 2025, we randomised 12,327 participants. Participants were 67% male with a mean (SD) age of 68 (11) years. Ischemic stroke was the index event for 95% of whom 27.4% had thrombolysis and/or mechanical thrombectomy. By TOAST classification, 43% of index strokes were LAA, 22% small vessel disease, 30% undetermined and 2% cardioembolic. Dual antiplatelets were planned in 63% as standard initial treatment. Trial completion is anticipated in October 2025. CONCLUSION: OCEANIC-STROKE will be the first completed trial of FXIa inhibition for prevention of stroke after non-cardioembolic stroke or TIA. TRIAL REGISTRATION: ClinicalTrials.gov (NCT05686070).